PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PERIKANAN NUSANTARA (PERSERO) CABANG SORONG - Edwar, Rizka Cintya; Amin, Muhammad; Harju, Leon Mitra (Gapenas Publisher, 2025)
This study aims to determine the effect of work environment and communication on employee work productivity at PT. Perikanan Nusantara (Persero) Sorong Branch. This study uses a quantitative method with a sample of 31 employees. Quantitative data used in this study using a Likert scale and the analysis used in this study is multiple linear regression analysis and then the data is processed using SPSS 20. The results of this study indicate that the work environment has a positive and significant effect on employee work productivity and communication has a positive and insignificant effect on employee work productivity.